2018
DOI: 10.3389/fpsyt.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Mental Health Care, Treatment Patterns, and Course of Psychosocial Functioning in Northern German Coronary Artery Disease Patients with Depressive and/or Anxiety Disorders

Abstract: BackgroundComorbid mental disorders in patients with coronary artery disease (CAD) are common and associated with adverse somatic outcomes. However, data on utilization rates of mental health care and treatment efficiency are scarce and inconsistent, which we tried to remedy with the present preliminary study on Northern German CAD patients.MethodA total of 514 German CAD patients, as diagnosed by cardiac catheterization, were assessed using the Mini International Neuropsychiatric Interview and the Global Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Similar results of female predominance of depressive symptoms as well as higher incidence of anxiety and CAD were reported in a Chinese study [25]. Another large study in 514 German CAD patients, evaluated by the Mini International Neuropsychiatric Interview and the Global Assessment of Functioning (GAF) scale demonstrated comorbidity of depression with CAD and treatment of the depression resulted in improvement of this condition [26]. Interestingly, patients undergoing CABG operation, depression and anxiety were increased after the operation compared to the pre-operative period [27].…”
Section: Discussionsupporting
confidence: 81%
“…Similar results of female predominance of depressive symptoms as well as higher incidence of anxiety and CAD were reported in a Chinese study [25]. Another large study in 514 German CAD patients, evaluated by the Mini International Neuropsychiatric Interview and the Global Assessment of Functioning (GAF) scale demonstrated comorbidity of depression with CAD and treatment of the depression resulted in improvement of this condition [26]. Interestingly, patients undergoing CABG operation, depression and anxiety were increased after the operation compared to the pre-operative period [27].…”
Section: Discussionsupporting
confidence: 81%
“…Lack of knowledge about the relevance of comorbid MD in CHD [ 6 , 14 , 15 ] may play a role. This may also depend on the type of MD, as Westermair et al [ 20 ] showed that the majority of CHD patients with comorbid depression received MD-related treatment, whereas there were deficits in diagnosis and treatment of comorbid anxiety disorders. Lack of trust in mental health care and stigmatising attitudes towards mental health on the part of physicians may also be involved [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, research on the quality of health care and treatment trajectories of patients with CHD and comorbid MD has been limited and inconsistent. For instance, there is one study showing that health care of comorbid depression is treated well in patients with coronary artery disease, while there are shortcomings in the diagnosis and treatment of comorbid anxiety disorders [ 20 ]. In contrast, other studies show that there are also deficits in depression management [ 17 , 18 ], in the implementation of treatment recommendations and in the diagnosis and treatment of MDs in general [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological interventions, such as cognitive-behavioral therapy, interpersonal psychotherapy, and problem-solving therapy, have shown promise in reducing depressive symptoms, improving treatment compliance, and preventing relapse when combined with medication (113). These interventions have led to gradual improvements in the condition of CHD patients (114).…”
Section: Interventionsmentioning
confidence: 99%